Contribution of Syeikh Tuan Minal in the Creative Islamic Civilization on Islamic Society in South Thailand - Awae Maeh Ouma; Abdullah Bin Yusuf Kareena (UIN Sunan Gunung Djati Bandung, 2014)
This paper aims to discuss the contributions of syeikh Tuan Minal in the creative of Islamic civilization on Islamic society in South Thailand. The related sources are collected using accounts, story and library. It uses qualitative analysis and criticism. The result shows that Syeikh Tuan Minal or Syeikh Zainal Abidin bin Muhammad al-Fatany is ulama from Patani achieving great complement and praises from other ulamas and general public. His activities are of great contribution to Muslim in patani in intelektual such as aqidah or Tauhid and fiqh, hadits, tasawuf and medicine. The works has been absorbed and still actualized in daily life until present day especially in terms of faith and worship.